2018
DOI: 10.1016/j.neuropharm.2017.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of dopamine in the differential neurotoxicity patterns of methamphetamine, mephedrone, methcathinone and 4-methylmethamphetamine

Abstract: Methamphetamine and mephedrone are designer drugs with high abuse liability and they share extensive similarities in their chemical structures and neuropharmacological effects. However, these drugs differ in one significant regard: methamphetamine elicits dopamine neurotoxicity and mephedrone does not. From a structural perspective, mephedrone has a β-keto group and a 4-methyl ring addition, both of which are lacking in methamphetamine. Our previous studies found that methcathinone, which contains only the β-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
(125 reference statements)
0
11
0
1
Order By: Relevance
“…These substances penetrate the neuron and cause a massive release of the neurotransmitter into the synaptic cleft. Studies in rodents show that amphetamines increase the levels of oxidative stress markers such as MDA, SOD, glutathione (GSH/GSSG), 2,3-dihydroxybenzoic acid in the cortex, corpus striatum [ 133 ], and hippocampus [ 134 ]. Moreover, toxic doses of methamphetamine inhibit the ETC, by interfering with all four complexes, in the corpus striatum , hippocampus , amygdala, nucleus caudatus , and prefrontal cortex , being incriminated in the development of neurodegenerative diseases [ 135 , 136 , 137 ].…”
Section: Resultsmentioning
confidence: 99%
“…These substances penetrate the neuron and cause a massive release of the neurotransmitter into the synaptic cleft. Studies in rodents show that amphetamines increase the levels of oxidative stress markers such as MDA, SOD, glutathione (GSH/GSSG), 2,3-dihydroxybenzoic acid in the cortex, corpus striatum [ 133 ], and hippocampus [ 134 ]. Moreover, toxic doses of methamphetamine inhibit the ETC, by interfering with all four complexes, in the corpus striatum , hippocampus , amygdala, nucleus caudatus , and prefrontal cortex , being incriminated in the development of neurodegenerative diseases [ 135 , 136 , 137 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, methylone (4 × 30 mg/kg at 2 hr intervals) can enhance putative damage to dopamine nerve endings as measured by decreases in DAT levels or binding more robustly in the presence of methamphetamine, yet oddly the same doses of MDPV appear to exert neuroprotective effects (Anneken et al 2015). More predictably, additive or synergistic neurotoxic effects have been shown when mephedrone is administered in combination with methamphetamine (Anneken et al 2018) or ethanol (Ciudad-Roberts et al 2016). Thus, there are highly complex mechanism of action of synthetic cathinones with regards to their ability to produce neurotoxic or monoamine-altering effects, and it is clear that such effects are dependent on a plethora of variables such, dose and frequency of administration, the presence of other drugs of abuse.…”
Section: Cellular Toxicity Induced By Synthetic Cathinonesmentioning
confidence: 99%
“…(Angoa-Perez et al 2012;Angoa-Perez et al 2014;Lopez-Arnau et al 2015;Martinez- Clemente et al 2014;Motbey et al 2012). On the other hand, some investigators have reported increases in astrocyte or microglia number in regions such as the frontal cortex, striatum or hippocampus following repeated high dose administration of mephedrone, methcathinone, or methylone(Anneken et al 2018;Lopez-Arnau et al 2014a;Lopez-Arnau et al 2014b)…”
mentioning
confidence: 99%
“…For many banned drugs, most notably mephedrone, the decision to ban was made without any real knowledge of its pharmacology let alone toxicology . This has since been rectified and mephedrone has been shown to lead to dopamine release but not to neurotoxicity . Similar research on synthetic cannabinoids is still relatively lacking…”
Section: Mephedronementioning
confidence: 99%
“…Heavy mephedrone use was associated with some deep depressive come‐downs that were thought to contribute to a few hanging suicides . Such behaviour is consistent with brain dopamine depletion since mephedrone has a major impact to release this neurotransmitter, although to my knowledge no measures of its concentration in the brain were made at postmortem, which represents a missed opportunity that is all too typical of research failings with new psychoactive substances.…”
Section: Mephedronementioning
confidence: 99%